Immunomodulatory properties of recombinant human granulocyte-macrophage colony-stimulating factor - G. M. Sysoeva; S. G. Gamaley; T. I. Esina; E. D. Danilenko (Медицинская иммунология, 2023)
Granulocyte-macrophage colony stimulating factor (GM-CSF) is a myelopoietic growth factor that exerts pleiotropic effect not only on the differentiation of immature progenitor cells into polymorphonuclear neutrophils, monocytes/macrophages and dendritic cells, but also controls the functioning of differentiated cells. GM-CSF is currently being investigated in clinical trials as an immunomodulator and adjuvant. However, a wide range of biological activities and, sometimes, paradoxical effects of this cytokine require more thorough studies of its action, in order to predict its efficacy under different conditions of immunotherapy. In this work, we have studied the effect of recombinant human GM-CSF on metabolic activity of mouse peritoneal exudate cells in primary cell cultures. Metabolic (redox) activity of the cells was assessed by their ability to reduce nitroblue tetrazolium (NBT) in the course of MF- and Fc-dependent phagocytosis triggered by addition of opsonized zymosan, or sheep erythrocytes to the culture medium. We have shown the dose-dependent stimulatory effect of GM-CSF on the oxidative metabolism of phagocytic peritoneal macrophages and neutrophils. Upon culturing the pepton-elicited cells at wide range of GM-CSF concentrations (5 to 40,000 ng/mL) for 2 and 24 hours, a more pronounced effect of the substance was observed for neutrophils. The GM-CSF preparation caused a significant increase (by 13-17%) in the redox activity of neutrophils induced by opsonized zymosan that persisted at a low dose range, and was retained after 24 hours. The stimulatory effect of GM-CSF on macrophages with NBT index increase by 16% was observed in the short-term cultures. In general, the elicited cells of both types showed a more pronounced response to lower concentrations of GM-CSF (5-125 ng/mL), and weaker effect at higher doses of the preparation. A similar dependence was found when studying the resident macrophages. Culturing of resident cells with GM-CSF at the doses of 5,000 to 40,000 ng/mL for 24 hours caused a significantly increased redox activity of the cells induced by zymosan, or sheep erythrocytes (by 33-52%). In both cases, the maximal response was detected at a dose of 5,000 ng/mL and decreased with increasing dose. The stimulatory effect of GM-CSF upon resident macrophages was more pronounced as compared to elicited cells, which was characterized by the prolonged period of cell activation (up to 24 hours of culture). The data obtained are of interest, in view of prospective usage of GM-CSF as a component of immunomodulatory and adjuvant therapy for various infectious diseases.